Acculturation and substance use in a Mexican American college student sample. Issue 3 (3rd July 2017) - Mercado, Alfonso; Ramirez, Maria; Sharma, Rachita; Popan, Jason; Avalos Latorre, Maria Luisa
ABSTRACT: Although the association between acculturation and substance use among Latino groups is important, it is often understudied, especially within specific Latino groups living in geographically distinct communities, such as the Mexican American population in South Texas. The researchers of this study aimed to better understand the effect of acculturation on substance use and alcohol dependence in a Mexican American college student population. This survey study investigated the correlation between acculturation and substance use and dependence by using the Vancouver Index of Acculturation (VIA), items related to substance use (nicotine, marijuana, and cocaine) in a Mexican American college student sample (N = 1, 494), and the Short Alcohol Dependence Data Questionnaire (SADD; N = 715). The study was conducted in the Texas–Mexico border region. The results suggest that higher levels of acculturation do not predict increased drug use or alcohol dependence in the Mexican American college students. However, acculturation was found to be associated with lower use of cocaine and marijuana. The discussion examines commonalities and differences in drug use and dependence. Specifically, acculturation seems to have an inverse relationship to substance use and may serve as a protective factor to licit and illicit drug use among Mexican American college students.